High-fidelity machine learning modelling of GO–Al₂O₃ assisted ethanol–MBD20 dual-fuel CI engine combustion - Klinmalee, Tossaphorn; Elumalai, P.V.; Alwetaishi, Mamdooh; Hussain, Fayaz; Chan, Choon Kit; Reddy, M. Venkateswar; Khan, Sher Afghan; Keçebas, Ali (Elsevier Ltd, 2026)
The implementation of ethanol-assisted dual-fuel operation in conjunction with nanoparticle-enhanced biodiesel combustion has garnered significant interest as an effective method for improving the efficiency and reducing the emissions of compression ignition (CI) engines. Most of the existing studies focus on these methods independently, thereby challenging the integration of data-driven optimisation with sustainability assessments. This experimental study examines the performance, emissions, and sustainability characteristics of a single-cylinder dual-fuel compression ignition engine with 20 vol% Chlorella vulgaris biodiesel (MB20), 5–15% ethanol energy share, and hybrid graphene oxide–aluminium oxide (GO–Al₂O₃) nanoparticles at 25–100 ppm. Of all the fuel Among the formulations analysed, MB20GA25E15 performed best, with a maximum brake thermal efficiency of 34.8% (6.1% over diesel) and 4.2% lower brake-specific fuel consumption. The CO levels were reduced by 18 to 22%, the concentrations of HC by 15 to 19%, and the smoke opacity measurements by 12 to 18%. However, a minor increase in NOₓ emissions (3–7%) was observed, associated with higher cylinder temperatures and additional available oxygen. Nine machine learning models were created to generalise and interpret the trends seen experimentally. Gradient boosting was the model that predicted the most accurately. The SHAP-based output analysis showed that engine load, ethanol share, and nanoparticle dosage are the main contributors to the results. Based on the Pugh matrix sustainability assessment, MB20GA25E15 is the best fuel blend, providing a balance among efficiency, emissions, cost, and environmental benefits. A practicable strategy for achieving sustainable operation is proposed: a CI engine consisting of a detailed framework based on experimental methods, machine learning, and sustainability principles for applying an ethanol-assisted microalgae biodiesel dual-fuel CI engine equipped with hybrid GO–Al₂O₃ nanoparticles.